Transmembrane Signaling in the Brain by Serotonin, A Key Regulator of Physiology and Emotion. Issue 5 (12th October 2005) - Adayev, Tatyana; Ranasinghe, Buddima; Banerjee, Probal
Abstract : Serotonin (5-HT) is an ancient chemical that plays a crucial functional role in almost every living organism. It regulates platelet aggregation, activation of immune cells, and contraction of stomach and intestinal muscles. In addition, serotonin acts as a neurotransmitter in the brain and the peripheral nervous system. These activities are initiated by the binding of serotonin to 15 or more receptors that are pharmacologically classified into seven groups, 5-HT1 through 5-HT7 . Each group is further divided into subgroups of receptors that are homologous but are encoded by discrete genes. With the exception of the 5-HT3 receptor-a cation channel—all of the others are G protein-coupled receptors that potentially activate or inhibit a large number of biochemical cascades. This review will endeavor to compare and contrast such signaling pathways with special attention to their tissue-specific occurrence, their possible role in immediate effects on covalent modification of other proteins, and relatively slower effects on gene expression, physiology and behavior.